SWAMI VIVEKANANDA’S EDUCATIONAL THOUGHT AND IT’S RELEVANCE IN CONTEXT WITH NEP 2020 - Singh, Keshav; Saxena, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Swami Vivekananda, a visionary philosopher and spiritual leader, articulated a comprehensive educational philosophy rooted in the holistic development of the individual and the nation. His ideas, emphasizing character building, self-reliance, and the integration of ancient wisdom with modern knowledge, remain profoundly relevant in contemporary India. This review article delves into the core tenets of Vivekananda’s educational thought, examining their alignment with the principles and objectives of the National Education Policy (NEP) 2020. By analyzing key themes such as the purpose of education, the role of the teacher, the importance of moral and spiritual development, and the significance of practical knowledge, this article highlights the enduring value of Vivekananda’s vision in shaping India’s educational landscape.